Impact of sub-acute acrolein inhalation on the molecular regulation of mitochondrial metabolism in rat lung. (1st April 2023) - Tulen, C.B.M.; Leermakers, P.A.; Schrieder, S.E.; van Schooten, F.J.; Opperhuizen, A.; Remels, A.H.V.
Abstract: Nowadays, mitochondria are recognized as key players in the pathogenesis of a variety of smoking-associated lung diseases. Acrolein, a component of cigarette smoke, is a known driver of biological mechanisms underlying smoking-induced respiratory toxicity. The impact of sub-acute acrolein inhalation in vivo on key processes controlling mitochondrial homeostasis in cells of the airways however is unknown. In this study, we investigated the activity/abundance of a myriad of molecules critically involved in mitochondrial metabolic pathways and mitochondrial quality control processes (mitochondrial biogenesis and mitophagy) in the lungs of Sprague-Dawley rats that were sub-acutely exposed to filtered air or 3 ppm acrolein by whole-body inhalation (5 h/day, 5 days/week for 4 weeks). Acrolein exposure induced a general inflammatory response in the lung as gene expression analysis revealed an increased expression of Icam1 and Cinc1 (p < 0.1; p < 0.05). Acrolein significantly decreased enzyme activity of hydroxyacyl-Coenzyme A dehydrogenase (p < 0.01), and decreased Pdk4 transcript levels (p < 0.05), suggestive of acrolein-induced changes in metabolic processes. Investigation of constituents of the mitochondrial biogenesis pathways and mitophagy machinery revealed no pronounced alterations. In conclusion, sub-acute inhalation of acrolein did not affect the regulation of mitochondrial metabolism and quality control, which is in contrast to more profound changes after acute exposure in other studies. Graphical Abstract: Created with Biorender.com. ga1 Highlights: Sub-acute acrolein exposure induces a general inflammatory response in rat lung. Sub-acute acrolein inhalation does not impact mitochondrial metabolism in lung. No alterations of mitochondrial quality control indices upon sub-acute acrolein inhalation.